PENGARUH PEMANFAATAN SISTEM KEUANGAN DESA DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KEUANGAN DANA DESA KOTA LHOKSEUMAWE - Dewi, Jesi Mahara; Arifai, Muhammad; Muzahid, Mukhlisul; Safaruddin, Safaruddin (Politeknik Negeri Lhokseumawe, 2025)
Abstract: This study aims to determine the Effect of the Utilization of the Village Financial System and Human Resource Competence on the Financial Accountability of Village Funds in Lhokseumawe City. The population in this study were all villages in Lhokseumawe City totaling 68 villages and the sample amounted to 68 villages in Lhokseumawe City with a sampling technique that is saturated sampling, with a total of 136 respondents, namely village heads and village treasurers. The data used are primary data where the data was obtained by distributing questionnaires directly to villages in Lhokseumawe City. The data analysis technique used is the Multiple Linear Regression Analysis method by conducting classical assumption tests, and hypothesis testing and testing using the SPSS IMB 27 statistical analysis tool. During the observation period, it showed that the research data was normally distributed and free from classical assumption problems. The results of this study indicate that the utilization of the village financial system and human resource competence have a significant effect on the financial accountability of village funds in Lhokseumawe City. Partially, the results indicate that the variables of village financial system utilization and human resource competency significantly influence the financial accountability of village funds in Lhokseumawe City. The influence of these two independent variables on the financial accountability of village funds in Lhokseumawe City is 31.2%, while the remaining 68.8% is explained by other factors not included in the study.Keywords: Village Financial System Utilization, Human Resource Competency, Village Fund Financial Accountability